Marginal Vertical Fit along the Implant-Abutment Interface: A Microscope Qualitative Analysis - Nicola Mobilio; Alberto Fasiol; Giulio Franceschetti; Santo Catapano (MDPI AG, 2016)
The aim of this study was to qualitatively evaluate the marginal vertical fit along two different implant-abutment interfaces: (1) a standard abutment on an implant and (2) a computer-aided-design/computer-aided-machine (CAD/CAM) customized screw-retained crown on an implant. Four groups were compared: three customized screw-retained crowns with three different "tolerance" values (CAD-CAM 0, CAD-CAM +1, CAD-CAM −1) and a standard titanium abutment. Qualitative analysis was carried out using an optical microscope. Results showed a vertical gap significantly different from both CAD-CAM 0 and CAD-CAM −1, while no difference was found between standard abutment and CAD-CAM +1. The set tolerance in producing CAD/CAM screw-retained crowns plays a key role in the final fit.